AN INVESTIGATION INTO LINGUISTIC FEATURES OF ANTITHESIS IN POLITICAL SPEECHES IN ENGLISH AND VIETNAMESE - Assoc. Prof. Phan Văn Hòa (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Antithesis can be explored in various aspects. However, this study limits itself to argumentation power of antithesis and stylistic features of rhetorical devices in antithesis in EPS and VPSs.